2011
DOI: 10.1590/s1807-59322011001000022
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal adiposity, insulin and bone quality in young male rats fed a high-fat diet containing soybean or canola oil

Abstract: OBJECTIVES:A low ratio of omega-6/omega-3 polyunsaturated fatty acids is associated with healthy bone properties. However, fatty diets can induce obesity. Our objective was to evaluate intra-abdominal adiposity, insulin, and bone growth in rats fed a high-fat diet containing low ratios of omega-6/omega-3 provided in canola oil.METHODS:After weaning, rats were grouped and fed either a control diet (7S), a high-fat diet containing soybean oil (19S) or a high-fat diet of canola oil (19C) until they were 60 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…Lower n6/n3 ratio induced reduction on body bone area and body bone mineral content (BMC), which is reflected in the lower spine area and spine BMC (Costa et al, (2012). However, the study by Costa et al (2011) showed an increase of 5% in the length of puppies who consumed high fat diet added with 19% of canola or soybean oil (fat diet) compared with the control group (7% of soybean oil). These findings showed that both the quantity and quality of dietary lipids interfer in puppies' length.…”
Section: Discussionmentioning
confidence: 98%
“…Lower n6/n3 ratio induced reduction on body bone area and body bone mineral content (BMC), which is reflected in the lower spine area and spine BMC (Costa et al, (2012). However, the study by Costa et al (2011) showed an increase of 5% in the length of puppies who consumed high fat diet added with 19% of canola or soybean oil (fat diet) compared with the control group (7% of soybean oil). These findings showed that both the quantity and quality of dietary lipids interfer in puppies' length.…”
Section: Discussionmentioning
confidence: 98%
“…4 The effects of fat tissue on bone health are far from clear: investigators have suggested that fat mass may or may not be associated with bone mass, directly via mechanical loading and indirectly via hormonal production by adipocytes. 5,6 Clinical and experimental studies have reported on the importance of α-linolenic acid (ALA, 18:3n-3)-rich diets for adiposity accumulation prevention and promotion of bone formation. Conversely, linoleic acid (LA, 18:2n-6) contributes to bone reabsorption and adipocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chronic intake of high-fat diet (HF) per se can be one independent factor to insulin resistance [ 3 ] . In previous studies, we observed higher glycemia and insulinemia in rats fed with HF diet containing 19 % canola oil [ 4 ] . However, the mechanisms of this alteration in glucose homeostasis remain not well explained.…”
mentioning
confidence: 72%
“…Retroperitoneal and epididymal fat depots were dissected and the mass was expressed as total (g) and fractional (g/100 g) (adjusted to total body mass). Based on serum analyses of glucose and insulin [ 4 ] , the homeostasis model assessment-insulin resistance (HOMA-IR) and HOMA of pancreatic β-cell function (HOMA-β) indexes were calculated, according to the following equations: The homeostasis model assessment of insulin resistance (HOMA-IR): [insulin (μIU/ml) × serum glucose (mmol/l)]/22.5; HOMA-β: [insulin (μIU/ml) × 20]/serum glucose (mmol/l)-3.5. HOMA-IR is more related to insulin resistance, while HOMA-β is related to insulin secretion [ 7 ] .…”
mentioning
confidence: 99%